1994
DOI: 10.2165/00002512-199404040-00004
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Quality of Life of Older Patients with Cancer

Abstract: Cancer in older people is an increasingly common problem. Since survival benefits may decline and the risks of treatment progressively increase with age, preservation and improvement of quality of life (QOL) is a major goal of geriatric oncology. The concept of health-related QOL holds that the preservation of health and physical function is necessary to the maintenance and improvement of QOL, and encompasses several constructs, including physical, functional, emotional, social, and spiritual domains. Several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
4

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 29 publications
0
13
0
4
Order By: Relevance
“…Therefore routine use outside studies appears not to be useful as the value of the information gained remains to be determined. However, QoL assessment is helpful in sensitizing physicians for patient problems [46][47][48].…”
Section: Quality Of Lifementioning
confidence: 99%
“…Therefore routine use outside studies appears not to be useful as the value of the information gained remains to be determined. However, QoL assessment is helpful in sensitizing physicians for patient problems [46][47][48].…”
Section: Quality Of Lifementioning
confidence: 99%
“…A number of studies have revealed age effects in the selection of screening evaluations and treatment procedures in various cancer samples (Guadagnoli et al, 1990; Liberati et al, 1991;Bennet et al, 1991). For the elderly, co-morbidity, shortened life expectancy and limitations in physical functioning are important considerations in medical decision making (Balducci, 1994). Treatment bias related to age has been reported by several authors (Greenfield et al, 1987;Grover et al, 1989;Silliman et al, 1989).…”
mentioning
confidence: 99%
“…Studies have confirmed that advancing age is associated with functional disabilities, dependence in activities of daily living (ADL), and greater co-morbidity (Goodwin et al, 1991;Lauria, 1991;Balducci, 1994). Other investigators reported no significant relationship between age and functional status (Vinokur et al, 1990;Ganz et al, 1992;Given et al, 1994).…”
mentioning
confidence: 99%
“…El dolor es el síntoma más frecuente y más temido en los pacientes ancianos con cáncer avanzado, al igual que para la población general. Puede producir por si mismo ansiedad, depresión, insomnio, astenia, anorexia, agitación y cambio en el estado mental; algunos factores, como el cansancio y la falta de sueño disminuyen el umbral del dolor, mientras que otros, como el dormir bien, la comprensión por parte de su entorno, la mejora del humor, las distracciones y el conocimiento de su situación, elevan dicho umbral [27][28][29] .…”
Section: Cuidados Paliativos Y Geriatría Más Allá De La Medicina Traunclassified